PENERAPAN TEORI-TEORI PENDIDIKAN UNTUK ANAK USIA DINI TERKAIT DALAM PENGEMBANGKAN KETERAMPILAN MOTORIK ANAK - Yudha Febrianta (LP2M Universitas Sarjanawiyata Tamansiswa, 2016)
Originally early childhood education to be held without programmed, especially in the family, and not based now increasingly required adequate knowledge about how children grow, develop and learn. The situation was still happening on the implementation of early childhood education in our country, even though research has shown how important provision since early childhood stimulation to optimize its development as an adult. Theories on Early Childhood Education will contribute a teacher in addressing the development of the child. In addition, teachers will know and understand how to give treatment at an Early Age Anaka. Then, with the understanding that all of it, especially in the field of how the teacher will provide activities in lanpangan melihan how the course will teach all the educational theory. Activities in the field is a series of activities to develop children's physical activity, especially motor skills.Keywords : theory of education , early childhood motor development